Conservative interventions may have little effect on reducing diastasis of the rectus abdominis in postnatal women – A systematic review and meta-analysis. (June 2023) - Benjamin, Deenika R.; Frawley, Helena C.; Shields, Nora; Peiris, Casey L.; van de Water, Alexander T.M.; Bruder, Andrea M.; Taylor, Nicholas F.
Abstract: Background: Diastasis of the rectus abdominis muscle (DRAM) commonly occurs in pregnancy and postnatally. Physiotherapists routinely guide women in its management, although the effectiveness of these treatments is unknown. Objectives: To determine the effectiveness of conservative interventions to reduce the presence and width of DRAM in pregnant and postnatal women. Data sources: EMBASE, Medline, CINAHL, PUBMED, AMED and PEDro searched until August 2021. Study selection/eligibility: Randomised control trials examining any conservative interventions to manage DRAM during the ante- and postnatal periods were included. Study appraisal and synthesis methods: Methodological quality was assessed using the Cochrane Risk of Bias 2 tool. Meta-analyses were performed using a random effects model to calculate mean differences (MD) and odds ratios (OR). A GRADE approach determined the certainty of evidence for each meta-analysis. Results: Sixteen trials with 698 women during the postnatal period were included. No trials evaluated interventions during the antenatal period. All interventions included some form of abdominal exercise. Other interventions included abdominal binding, kinesiotape and electrical stimulation. There was moderate certainty evidence from six trials (n = 161) that abdominal exercise led to a small reduction in inter-recti distance (MD −0.43 cm, 95% CI −0.82 to −0.05) in postnatal women compared to usual care. Limitations: Three of the 16 trials had a low risk of bias. Conclusion and implications: Conservative interventions do not lead to clinically significant reductions in inter-recti distance in women postnatally but abdominal exercises may have other physical and psychosocial benefits in the management of DRAM. Systematic Review Registration Number PROSPERO (CRD42020172529).